Effect of elevated temperature on the growth, physiological, and yield-related traits of commercial rice in Malaysia - Gomathy Sethuraman,; Normaniza Osman,; Acga, Cheng; Wickneswari Ratnam,; Mohd Razi Ismail,; Nurul Amalina Mohd Zain, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Rising temperatures from climate change threaten rice production, impacting livelihoods, global food security, and the sustainability of feeding a growing population. Unlike most studies focusing on specific growth stages, this study investigated the effects of 35 °C (T35) and 36 °C (T36) on the growth, physiological traits across all growth stages and yield-related traits of four Malaysian rice varieties - Sempadan 303 (S303), Sebernas 307 (S307), UKMRC02 (RC02), and UKMC09 (RC09) – compared to MR219, a high-yielding variety. Elevated temperature observed significant differences in plant height (PH), leaf area index (LAI), 100-filled grain weight (100GW), filled grain (FG), grain to leaf area ratio (GToLAI), and several grain nutrients in rice varieties. LAI correlated positively with PH (R2=0.723**) and stomatal conductance (R2=0.672**). All varieties recorded higher relative chlorophyll content at 126 days after sowing (DAS) surpassing values at 90 DAS and were significantly higher in T36 for MR219 and S303 showing adaptation to elevated temperature. The harvest index was higher in T36 across all varieties, except RC02, which had a lower FG. All varieties showed no significant difference in Mg, Al, and Si, although MR219 and RC09 had lower P and K in T36. Ca was higher in T36 for all varieties except MR219. This study highlights the varied growth, physiological, and yield-related responses of Malaysian rice varieties to elevated temperatures, with MR219, S303, and RC09 showing strong adaptation due to better stress-coping mechanisms such as maintaining higher LAI, 100GW, HI, and Ca, while S307 and RC02 demonstrated susceptibility.